A realidade das organizações da sociedade civil de interesse público na região de Itapeva - São Paulo - Raifur, Marcelo (2011)
This work has as thematic the Law No. 9790/99 establishing the qualification of Civil Society Organization of Public Interest - OSCIP, allowing a new form of relationship between the organizations credentialed by the Ministry of Justice and the Government allowing signing a partnership agreement. Decree Law 7568/2011, recently promulgated, amends the rules for carrying out a partnership agreement, that may be experienced by organizations that do not fit the new rules. Based on the aforementioned laws and a historical development of the Third Sector for the period from 1543 Brazilian (Brazil Empire) to 2001 was possible to verify the legal ways offered to NGOs and visualize the major impacts generated by their developments. Through a qualitative nature methodology, also considering quantitative data, through analysis of documents, publications, interviews and having as scope institutions qualified as OSCIP found in the municipalities of Itaberá, Itapeva and Guapiara, all of them located in Southeastern side of Sao Paulo state, were analyzed. We conclude after collected data analysis that the experienced relationship of these entities with the Government in dealing with the "Partnership Agreement" in fact does not happen as foreseen in the law, wich is caused by mere ignorance of the lagislation by Public Managers and especially by the absence of projects from organizations that attract the interest of the State.